Relationship between microstructures and grain-scale trace element distribution in komatiite-hosted magmatic sulphide ores - Vukmanovic, Zoja; Reddy, Steven; Godel, B.; Barnes, S.; Fiorentini, M.; Barnes, S.; Kilburn, M.R. (Elsevier BV, 2014)
Komatiite-hosted nickel sulphides from the Yilgarn Craton (Australia) consist of two main sulphide phases: pyrrhotite (Fe7S8) and pentlandite ((Fe,Ni)9S8); two minor sulphide phases: chalcopyrite (CuFeS2) and pyrite (FeS2) and trace arsenides. Samples of massive sulphides from three deposits with diverse deformation and metamorphic histories (the Silver Swan, Perseverance and Flying Fox deposits) have been studied by electron backscatter diffraction and laser ablation inductively coupled plasma mass spectrometry and nano-scale secondary ion mass spectrometry. These ore bodies were selected to investigate the relationship between microstructures and mineral trace element chemistry in three dominant sulphide species in each deposit. In all three samples, pyrrhotite preserves a strong evidence of crystal plasticity relative to both pentlandite and pyrite. The trace element composition of pyrrhotite shows significant variation in specific elements (Pb, Bi and Ag). This variation correlates spatially with intragrain pyrrhotite microstructures, such as low angle and twin boundaries. Minor signatures of crystal plasticity in pyrite and pentlandite occur in the form of rare low angle boundaries (pentlandite) and mild lattice misorientation (pyrite). Trace element compositions of pentlandite and pyrite show no correlation with microstructures.Variations in pyrrhotite are interpreted as a result of intragrain diffusion during the syn- and post-deformation history of the deposit. Intragrain diffusion can occur either due to bulk diffusion, dislocation–impurity pair diffusion, or by “pipe diffusion”, i.e. along fast diffusion pathways at high and low angle, and twin boundaries. This contribution examines three different diffusion models and suggests that dislocation–impurity pair diffusion and pipe diffusion are the most likely processes behind increased trace element concentration along the microstructures in pyrrhotite. The same phenomenon is observed in samples from three different deposits that experienced widely different metamorphic conditions, implying that the final disposition of these elements reflects a post peak-metamorphic stage of the geological history of all three deposits.